Respuesta :
Step-by-step explanation:
Hey there!
Given;
f ( x ) = x² + 2x - 1
g ( x ) = 3x - 2
To verify:
[tex]( \frac{f}{g} )(2) = \frac{f(2)}{g(2)} [/tex]
LHS:
[tex] (\frac{f}{g} )(x) = \frac{ {x}^{2} + 2x - 1}{3x - 2} [/tex]
~ Insert "2" instead of "x".
[tex] (\frac{f}{g} )(2) = \frac{ {2}^{2} + 2 \times 2 - 1 }{3 \times 2 - 2} [/tex]
Simplify it;
[tex] \frac{f}{g} (2) = \frac{4 + 4 - 1}{6 - 2} [/tex]
Therefore; (f/g)(2) = 7/4.
RHS:
[tex] \frac{f(x)}{g(x)} = \frac{ {x}^{2} + 2x - 1}{3x - 2} [/tex]
~Insert "2" instead of"x".
[tex] \frac{f(2)}{g(2)} = \frac{ {2}^{2} + 2 \times 2 - 1 }{3 \times 2 - 2} [/tex]
Simplify it.
[tex] \frac{f(2)}{g(2)} = \frac{4 + 4 - 1}{6 - 2} [/tex]
Therefore, f(2)/g(2) = 7/4.
Since (f/g)(2) = f(2)/g(2) = 7/4.
Proved!
Hope it helps!
Step-by-step explanation:
- f(x) = x² + 2x - 1
- g(x) = 3x - 2
Soo :
[tex] \tt( \frac{f}{g} )(2) = \frac{f(2)}{g(2)} [/tex]
[tex] \tt( \frac{ {x}^{2} + 2x - 1 }{3x - 2} )(2) = \frac{ {2}^{2} + 2(2) - 1 }{3(2) - 2} [/tex]
[tex] \tt( \frac{ {2}^{2} + 2(2) - 1}{3(2) - 2} )= \frac{7}{4} [/tex]
[tex] \boxed{ \tt \frac{7}{4} = \frac{7}{4} }[/tex]
Soo true.